Prevention of COVID-19 in Thoracic Surgery Patients: Lessons Learned during the First Pandemic Wave - Stoleriu, Mircea Gabriel; Gerckens, Michael; Ströh, Katja; Kovács, Julia; Samm, Nicole; Obereisenbuchner, Florian; Hetrodt, Justin; Schmidt, Felicitas Maria; Reinmuth, Niels; Heiß-Neumann, Marion; Stacher-Priehse, Elvira; Koch, Ina; Behr, Jürgen; Ketscher, Christian; Grützner, Uwe; Hatz, Rudolf (Pneumologie, 2021)
Background The aim of this retrospective study was to investigate the implementation of measures to prevent perioperative COVID-19 in thoracic surgery during the first wave of the COVID-19 pandemic 2020 allowing a continued surgical treatment of patients. Methods The implemented preventive measures in patient management of the thoracic surgery department of the Asklepios Lung Clinic Munich-Gauting, Germany were retrospectively analyzed. Postoperative COVID-19 incidence before and after implementation of preventive measures was investigated. Patients admitted for thoracic surgical procedures between March and May 2020 were included in the study. Patient characteristics were analyzed. For the early detection of putative postoperative COVID-19 symptoms, typical post-discharge symptomatology of thoracic surgery patients was compared to non-surgical patients hospitalized for COVID-19.Results Thirty-five surgical procedures and fifty-seven surgical procedures were performed before and after implementation of the preventive measures, respectively. Three patients undergoing thoracic surgery before implementation of preventive measures developed a COVID-19 pneumonia post-discharge. After implementation of preventive measures, no postoperative COVID-19 cases were identified. Fever, dyspnea, dry cough and diarrhea were significantly more prevalent in COVID-19 patients compared to normally recovering thoracic surgery patients, while anosmia, phlegm, low energy levels, body ache and nausea were similarly frequent in both groups.Conclusions Based on the lessons learned during the first pandemic wave, we here provide a blueprint for successful easily implementable preventive measures minimizing SARS-CoV-2 transmission to thoracic surgery patients perioperatively. While symptoms of COVID-19 and the normal postoperative course of thoracic surgery patients substantially overlap, we found dyspnea, fever, cough, and diarrhea significantly more prevalent in COVID-19 patients than in normally recovering thoracic surgery patients. These symptoms should trigger further diagnostic testing for postoperative COVID-19 in thoracic surgery patients.